PENGARUH PEMBANGUNAN TOL SOLO-YOGYA TERHADAP KINERJA SIMPANG BERSINYAL - Hermani, Wahyuningsih Tri; Setyawan, Ary; Yulianto, Budi; Hanung Triyono, AR. (Direktorat Bina Teknik Jalan dan Jembatan, 2024)
The construction of the Solo-Yogyakarta toll road is part of the National Strategic Project. At the construction stage, toll road infrastructure needs to assess the impact of traffic on surrounding roads and intersections, considering the many security and safety problems. Road performance evaluation is critical to overcome traffic problems that may arise during toll road operations in the future. This research aims to calculate traffic performance at signalized intersections, which are influenced by the construction of the Solo-Yogya toll road. The locations studied were four signalized intersections on the Solo-Yogya toll road using primary data on the number of vehicles, travel time, and vehicle speed. The performance of signalized intersections is calculated using the 2023 Indonesian Road Capacity Guidelines, while the distribution of future movements is carried out using JICA STRADA Software and the Gravity model with applicable toll road rates. The traffic growth is 5.6% per year, according to data on the number of vehicles in Jawa Tengah Dalam Angka. The performance of signalized intersections after constructing the Solo-Yogya toll road in 2022 has an average Volume Capacity Ratio (VCR) value of 0.78. In 2046, it will be 1.47. At intersection-3 Bangak Barat and intersection-4 Condong Catur, building an Interchange before 2032 is recommended. The recommendation is to reduce vehicle delays, as in 2032, the VCR value will be more than 0.8. The study gives insight into the combined methods of forecasting traffic growth on signalized intersections near freeways. Keywords: traffic performance, JICA STRADA, gravity model, signalized intersection capacity, APILL